The quality of received drug therapy in patients with stable coronary heart disease according to the ALIGN (TherApy in stabLe Coronary Artery dIsease Patients According to Clinical GuideliNes) study - E. D. Zharkova; S. Yu Martsevich; Yu. V. Lukina; N. P. Kutishenko; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To assess the adherence to prescribed treatment and the stability of the effect achieved after 3 months to improve the quality of therapy in patients with stable coronary heart disease after 12 months of follow-up. Material and methods. 73 patients with confirmed stable coronary heart disease were included in the study. The study included 3 patient visits: an initial treatment visit (V0) with an assessment of baseline blood pressure (BP), low-density lipoprotein cholesterol (LDL cholesterol), patient adherence to therapy and with therapy correction; a repeat visit (V1) after 3 months — an assessment of the quality of therapy received by the patient and achievement of the target BP and LDL cholesterol, a visit after 12 months (V2) with an assessment of the results achieved, the therapy received and adherence to treatment. 57 patients (47 men and 10 women) were examined at the V2 visit. 14 (19,2%) patients withdrew their consent to participate in the study after the initial treatment (visit V0), 1 patient died due to cancer, 1 patient died due to cardiovascular disease. The response was 80,8%.Results. After the visit of repeated correction of therapy (V1) after 9 months of follow-up, a high frequency of drug therapy was observed, including 59% of patients taking medications of 4 main groups according to clinical recommendations. Among patients with arterial hypertension, there is a preservation of the result of achieving the target level of blood pressure (87% of patients), a statistically insignificant decrease in the frequency of achieving the target level of LDL cholesterol to 44,2% compared with the previous result of 53,7%. There was a tendency to improve the overall absolute adherence (increase by 10%, p=0,2) of patients to treatment.Conclusions. The possibility of constant contact of the patient with the doctor of the specialized cardiological unit of the scientific center and timely correction of the therapy allowed to maintain the achieved results and increase the overall adherence of patients to treatment.